Bibliometric analysis of research on intestinal flora and primary biliary cholangitis published between 2004 and 2024 using VOSviewer and CiteSpace visualization - Tao Li; Wang Jing (Frontiers in Medicine)
BackgroundIncreasing evidence suggests that the onset and progression of primary biliary cholangitis (PBC) are closely linked to changes in gut microbiota, including bacterial translocation, molecular mimicry, and immune regulation. This study aimed to conduct a bibliometric analysis of the frontiers and hotspots of research on the relationship between gut microbiota and PBC between 2004 and 2024.MethodsA bibliometric study was conducted by searching the Web of Science database for articles on intestinal flora and PBC published between 2004 and 2024. Excel, VOSviewer, and CiteSpace were used for econometric analysis and visualization of the identified articles.ResultsBetween 2004 and 2024, 167 articles focusing on intestinal flora and PBC were published. The number of publications in this field maintained an upward trend over the years, with China and the United States contributing the highest number of articles. The United States had the highest total number of citations, and the institution with the most publications in the United States was the University of California Davis, with the team led by Professor Gershwin contributing the greatest number of articles. Frontiers in Immunology had the highest number of articles in the field, while Nature had the highest impact in terms of publications in this area of research. The main keywords were “primary sclerosing cholangitis,” “bile acids,” “ursodeoxycholic acid,” “cirrhosis,” “farnesoid X receptor,” “inflammatory bowel disease,” “risk factors,” and “liver disease.”ConclusionThere is a correlation between gut microbiota and PBC, and the role of gut microbiota in the pathogenesis and treatment of PBC will continue to be a future research direction. Targets such as bile acids and farnesoid X receptors are also current research hotspots.